2000
DOI: 10.1046/j.1471-4159.2000.0742373.x
|View full text |Cite
|
Sign up to set email alerts
|

gp120 Induces Cell Death in Human Neuroblastoma Cells Through the CXCR4 and CCR5 Chemokine Receptors

Abstract: Abstract:To infect target cells, the human immunodeficiency virus (HIV) type I (HIV-1) must engage not only the well-known CD4 molecule, but it also requires one of several recently described coreceptors. In particular, the CXCR4 (LESTR/fusin) receptor allows fusion and entry of T-tropic strains of HIV, whereas CCR5 is the major coreceptor used by primary HIV-1 strains that infect macrophages and CD4ϩ T-helper cells (M-tropic viruses). In addition, the ␣ chemokine SDF1␣ and the ␤ chemokines MIP1␣, MIP1␤, and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 48 publications
(57 reference statements)
11
94
0
Order By: Relevance
“…Several studies have reported the neurotoxic effect of gp120 in vitro and in vivo and the involvement of chemokine receptors in this process (Catani et al, 2000;Hesselgesser et al, 1998;Kaul and Lipton, 1999;Meucci and Miller, 1996;Pandey and Bolsover, 2000;Zheng et al, 1999). In line with these reports, treatment of SH-SY5Y cells with gp120 IIIB (200 pM) resulted in significant, albeit moderate, cell death (Figure 1), which was blocked by pretreatment with AMD3100 (100 ng/ml).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Several studies have reported the neurotoxic effect of gp120 in vitro and in vivo and the involvement of chemokine receptors in this process (Catani et al, 2000;Hesselgesser et al, 1998;Kaul and Lipton, 1999;Meucci and Miller, 1996;Pandey and Bolsover, 2000;Zheng et al, 1999). In line with these reports, treatment of SH-SY5Y cells with gp120 IIIB (200 pM) resulted in significant, albeit moderate, cell death (Figure 1), which was blocked by pretreatment with AMD3100 (100 ng/ml).…”
Section: Resultssupporting
confidence: 74%
“…CXCR4 is the specific receptor for the chemokine CXCL12 (previously known as SDF-1), which orchestrates the development of many areas of the brain as well as other tissues (Lazarini et al, 2003;Tran and Miller, 2003;Zou et al, 1998). CXCR4 can also bind the human immunodeficiency virus (HIV) envelope protein gp120 that induces apoptotic cell death in primary neurons and cell lines (Bachis and Mocchetti, 2004;Catani et al, 2000;Hesselgesser et al, 1997;Kaul and Lipton, 1999;Mattson et al, 2005;Meucci and Miller, 1996). Despite a convincing role of gp120 in the apoptosis of neurons, the effects of CXCL12 on neuronal survival remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Soluble gp120 can induce apoptosis in lymphocytes, 12 but also in neurones, [24][25][26][27] cardiomyocytes, 17,28 kidney epithelial cells 29,30 and hepatocytes. 31 These potent cytotoxic effects have been implicated in the HIV-1-induced lymphodepletion, HIV-associated dementia (also called HIV encephalitis or neuro-AIDS), AIDS-cardiomyopathy, as well as AIDS associated nephropathy and hepatopathy.…”
Section: Cell Killing By Soluble Gp120mentioning
confidence: 99%
“…This issue has been herein addressed having as an experimental model the human neuroepithelioma cell line CHP-100 [13]: CXCR4, in fact, is constitutively expressed by CHP-100 cells [14] and, in this system, it has been reported to mediate CXCL12-induced chemotaxis [8].…”
Section: Introductionmentioning
confidence: 99%